Teaching by priciples: an interactive approach to language pedagogy / H. Douglas Brown - H. Douglas, Brown
The book synthesizes that accumulation of knowledge into parctical, principled approach to teaching English as a second or foreign language. It is a book for prospective and new teachers who essentially need to learn how to walk into classroom full of learners adn effectively accomplish communicative objectives. It primarily addresses the need of those in teacher education programs who have never taught before, but it secondarily serves as a refresher course for these who have some experience in the classroom. The book speaks both to those who are in English as a second language contexts (in English-speaking countries) and to those whoa re in English as a foreign language situations. Amd the book is designed to be read and studied and enjoyed by those with little or no previous work in liguistics, psychology, or second language acquisition.